Risk factors associated with gallstone disease - Dhamnetiya, Deepak; Goel, Manish Kumar; Dhiman, Balraj; Pathania, Om Prakash (Indian Journal of Community Health, 2018)
Background: Gallstone disease is one of the most common abdominal conditions for which patients are admitted in surgical wards of hospitals. Aim & Objective: The study was conducted to understand the association between behavioral and personal factors and gall stone disease among study subjects. Settings & Design: a case-control study conducted in a tertiary care hospital of New Delhi. Material & Methods: 120 each of cases and controls of over 20 years, matched for age and sex were recruited in the study. Data collection was done on a self-designed pretested “interview schedule.” Statistical analysis: The observations have been described in terms of mean and standard deviation for continuous data. To measure the strength of association simple Odd’s Ratio (OR) was calculated and McNemar’s test was used for matched pair analysis. Binary logistic regression was used for multivariate analysis to find out different correlates and analyses the independent effects of these correlates on GSD. Results: weight (59.20±9.57), height (159.67±6.25), BMI (23.20±3.15), waist circumference (75.79±7.07) and W/H ratio (0.80±0.06) were significantly higher [as seen by applying student t test] in cases as compared to controls 54.84±7.02, 156.58±4.93, 21.95±2.81, 73.49±6.09 and 0.77±0.05 respectively. High parity [OR-5.75, 95% CI 1.99-16.63] had the strongest association followed by high W/H ratio [OR-5.25, 95% CI 1.80-15.29], sedentary physical activity [OR-4.75, 95% CI 2.22-10.18], smoking [OR-3.4, 95% CI 1.25-9.21], consumption of smokeless tobacco [OR-2.36, 95% CI 1.17-4.78] and high BMI [OR-1.71, 95% CI1.03-2.83]. Conclusion: High parity, High W/H ratio, Physical inactivity, Current smoking, Smokeless tobacco and high BMI were found to be risk factors for the development of gallstone disease.